Seismic Site Response, Analysis and Characterization of Major Cities in UAE - Irfan, Muhammad (2011)
A Master of Science Thesis in Civil Engineering submitted by Muhammad Irfan entitled, "Seismic Site Response, Analysis and Characterization of Major Cities in UAE," submitted in June 2011. Available are both soft and hard copies of the thesis.